2007
DOI: 10.1086/519562
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dissection of Isolated Disease Features in Mosaic Neurofibromatosis Type 1

Abstract: Elucidation of the biological framework underlying the development of neurofibromatosis type 1 (NF1)-related symptoms has proved to be difficult. Complicating factors include the large size of the NF1 gene, the presence of several NF1 pseudogenes, the complex interactions between cell types, and the NF1-haploinsufficient state of all cells in the body. Here, we investigate three patients with distinct NF1-associated clinical manifestations (neurofibromas only, pigmentary changes only, and association of both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(103 citation statements)
references
References 45 publications
3
98
0
2
Order By: Relevance
“…The aggregated data obtained from all patients with mosaic NF1 clearly indicate that the percentage of cells carrying the NF1 first hit mutation is often too low to be reliably detected in blood by a Sanger approach. 30 The frequency of mosaicism in sporadically affected NF1 patients is currently still largely unknown. 36 We also showed that our NGS NF1 mutation-screening strategy can be applied to tumour analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aggregated data obtained from all patients with mosaic NF1 clearly indicate that the percentage of cells carrying the NF1 first hit mutation is often too low to be reliably detected in blood by a Sanger approach. 30 The frequency of mosaicism in sporadically affected NF1 patients is currently still largely unknown. 36 We also showed that our NGS NF1 mutation-screening strategy can be applied to tumour analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This peculiar mosaic-localized form of NF1 may explain the absence of detectable somatic NF1 mutation in blood. [29][30][31] Detection of mutations in homopolymeric stretches In the seven cytosine homopolymeric stretch, wild-type control samples recurrently showed artifact deletions of one cytosine with a mean 6.1% MAF and artifact duplication with a mean 4.7% MAF (Supplementary Figure S6). The 10 true-positive duplications (control samples) were observed with a mean 38.3% MAF.…”
Section: Validation Of Methodsmentioning
confidence: 99%
“…6 In contrast, investigation of humans with mosaic NF1 mutations shows that neurofibromas and Café-au-lait macules appear also within a wild-type background. 7 In addition, other factors such as the time point of biallelic inactivation or the expression of modifier genes seem to influence the formation of neurofibromas. 8 Although these studies support a 'second-hit' hypothesis to explain the origin of NF1 tumors, they also stress the importance of the permissive tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…This excess of deletions is probably due to an ascertainment bias since mosaic NF1 microdeletions are relatively easy to identify at the individual cell level using FISH analysis. By contrast, the detection of mosaicism for a nucleotide substitution within the NF1 gene is much more difficult, particularly if cells bearing the mutation are present at low levels [Maertens et al, 2007]. So far, the majority of reported mosaic NF1 microdeletions have been either atypical or type-2 [reviewed in KehrerSawatzki and Cooper, 2008].…”
Section: Introductionmentioning
confidence: 99%